Dual SIFamide receptors in Ixodes salivary glands - Guerrib, Fetta; Ning, Caina; Mateos-Hernandéz, Lourdes; Rakotobe, Sabine; Park, Yoonseong; Hajdusek, Ondrej; Perner, Jan; Vancová, Marie; Valdés, James J; Šimo, Ladislav (Insect biochemistry and molecular biology, 2023)
Salivary glands are vital to tick feeding success and also play a crucial role in tick-borne pathogen transmission. In previous studies of Ixodes scapularis salivary glands, we demonstrated that saliva-producing type II and III acini are innervated by neuropeptidergic axons which release different classes of neuropeptides via their terminals (Šimo et al., 2009b, 2013). Among these, the neuropeptide SIFamide-along with its cognate receptor-were postulated to control the basally located acinar valve via basal epithelial and myoepithelial cells (Vancová et al., 2019). Here, we functionally characterized a second SIFamide receptor (SIFa_R2) from the I. scapularis genome and proved that it senses a low nanomolar level of its corresponding ligand. Insect SIFamide paralogs, SMYamides, also activated the receptor but less effectively compared to SIFamide. Bioinformatic and molecular dynamic analyses suggested that I. scapularis SIFamide receptors are class A GPCRs where the peptide amidated carboxy-terminus is oriented within the receptor binding cavity. The receptor was found to be expressed in Ixodes ricinus salivary glands, synganglia, midguts, trachea, and ovaries, but not in Malpighian tubules. Investigation of the temporal expression patterns suggests that the receptor transcript is highly expressed in unfed I. ricinus female salivary glands and then decreases during feeding. In synganglia, a significant transcript increase was detected in replete ticks. In salivary gland acini, an antibody targeting the SIFa_R2 recognized basal epithelial cells, myoepithelial cells, and basal granular cells in close proximity to the SIFamide-releasing axon terminals. Immunoreactivity was also detected in specific neurons distributed throughout various I. ricinus synganglion locations. The current findings, alongside previous reports from our group, indicate that the neuropeptide SIFamide acts via two different receptors that regulate distinct or common cell types in the basal region of type II and III acini in I. ricinus salivary glands. Our study investigates the peptidergic regulation of the I. ricinus salivary gland in detail, emphasizing the complexity of this system.
Keywords: Synganglion; Animals; SIFamide receptors; Salivary gland acini; Female; slinné žlázy; klíště; SIFamide; Salivary Glands; ženské pohlaví; sliny; neurony; Neurons; Ticks; Saliva; Neuropeptides; neuropeptidy; zvířata; Ixodes